PENGARUH HARGA, PROMOSI, KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN JASA OJEK ONLINE â€œOM-JEKâ€ JEMBER - Anggriana, Rina; Qomariah, Nurul; Santoso, Budi (Jurnal Sains Manajemen dan Bisnis Indonesia, 2017)
ABSTRACTBusiness services today are increasingly diverse in order to meet the needs of people's lives. Business services is one business that strives to create customer satisfaction. One of the services business that is developing at this time is the business of two-wheeled transpotation services or often referred to by the name of motorcycle taxi. The purpose of this study is to determine and analyze the influence of price, promotion, quality of service to customer satisfaction partially. The population in this study is the customer "Om-Jek" Jember. This research includes quantitative research with survey method. The type of data used is primary data collected through the dispersion of cross-polled by using purposive sampling method and the sample number of 95 respondents. This research uses multiple linear regression tool. The results showed that the variable price, promotion, service quality influence on customer satisfaction online ojek service "Om-Jek" Jember. Each variable has a positive and significant impact on customer satisfaction of online ojek service "Om-Jek" Jember.Keywords: Price, Promotion, Service Quality And Customer Satisfaction